Migration, the perception of security risks and media interpretation frameworks in Croatia and Hungary - Cvrtila, Vlatko (Array, 2019)
Although they are the most vulnerable group of people, immigrants are often perceived as a threat, with immigration and terrorism issues put under a common denominator. Political discourse and mass media are contributing factors, which, when framing migrants as a threat and emphasizing the connection with terrorism in their reporting, can affect the perception of public safety risks. Framing migrants as a terrorist risk has a negative impact on migration-related policies, changing focus from humanitarian towards security issues. The European Union’s migration policy is humanitarian, but it is reconsidered by individual member states defining migration as a risk. In these countries, measures to prevent terrorism include the acceptance of restrictive immigration policies, e.g. in Hungary. In the process of securitization, migrants are interpreted as a risk and threat to the survival of traditional identity values. This problem is analysed through examples of Hungary, a country with an exceptionally restrictive migration policy, and neighbouring Croatia which was perceived as a transitional country for migrants and refugees on their way West during the European migration crisis in 2015 and 2016, much like Hungary. For this purpose, several components are considered: the results of longitudinal Eurobarometer surveys that can determine public opinion changes in EU member states, the trends and results of the Hungarian referendum on migration quotas from October 2016, and the selected research and analysis of trends and media coverage of this issue in media. It is an attempt to determine whether and to what extent the public, political authorities and media in Croatia and Hungary referred to “unintentional” or „forced migrants“ as the negative non- European Other, during the European migration crisis.